Influência da suplementação com licopeno sobre o comprometimento renal na obesidade induzida por dieta em ratos: análise do perfil bioquímico, funcional e morfológico - Ghiraldeli, Luciana [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
Introdução. A obesidade está relacionada com o desenvolvimento de várias doenças, entre elas a doença renal crônica. O licopeno é um carotenoide presente no tomate e em outros vegetais e é um dos compostos antioxidantes mais potentes dentre os carotenoides. Vários estudos tem investigado o efeito protetor do licopeno em inúmeras doenças. Entretanto, para o nosso conhecimento, poucos estudos abordaram o efeito do licopeno sobre as alterações renais associadas à obesidade. Objetivo. O objetivo geral do presente estudo será o de verificar a influência da suplementação com licopeno sobre o comprometimento bioquímico, funcional e morfológico renal em modelo experimental de obesidade induzida por dieta rica em carboidratos simples e gordura saturada. Método. Ratos Wistar (n= 40) randomizados em dois grupos: Controle (C, n=20) - dieta padrão + água ou Obeso (Ob, n=20) - dieta hipercalórica + água acrescida de sacarose 25% por 20 semanas. Na 20ª semana foi detectada insuficiência renal por meio de avaliação bioquímica urinária (proteinúria) e os animais foram redistribuídos em 4 grupos: Controle (C, n=10); Controle+Licopeno (C+Li, n=10); Obeso (Ob, n=10); Obeso+Licopeno (Ob+Li, n=10). Os animais receberam óleo de milho (C, C+Li) ou licopeno (10 mg/kg peso/dia) (Ob, Ob+Li) via gavage por 10 semanas adicionais. Na 30ª semana foram submetidos à coleta de urina de 24 horas, aferição de pressão arterial sistólica e à eutanásia para coleta de sangue e rins. Avaliados os seguintes parâmetros: índice de adiposidade, dosagens bioquímicas plasmática (glicose, insulina, ureia, creatinina, proteína total, albumina, e urinárias (proteínas totais, albumina, ureia, creatinina); cálculo do índice de Homa-IR, biomarcadores do dano oxidativo renal (carbonilação de proteínas e lipoperoxidação), análise do licopeno renal e análise histológica renal. Resultados. O modelo de dieta adotado promoveu obesidade nos grupos obesos (Ob e Ob+Li) em relação aos grupos controles (C e C+Li). Os animais obesos (Ob e Ob+Li) exibiram maior nível de pressão arterial sistólica, glicose sérica, e albumina plasmática em relação aos grupos controles (C e C+Li). Insulina plasmática, índice HOMA-IR, índice urinário proteína/creatinina, carbonilação de proteínas de tecido renal que se mostraram aumentados nos animais do grupo obeso foram reduzidos com a suplementação com licopeno (Ob vs Ob+Li). A análise histológica renal mostrou aumento de depósito de gordura (lipidose) tubular nos animais do grupo Obeso e diminuído com a suplementação com licopeno (Ob vs Ob+Li). Conclusões. O modelo de dieta adotado promoveu obesidade (índice de adiposidade), aumento de pressão arterial, glicose sérica e albumina plasmática sem influência da suplementação com o carotenoide. Por outro lado, o aumento de insulina sérica, índice HOMA-IR, índice urinário proteína/creatinina, carbonilação de proteínas de tecido renal e depósito de gordura renal (lipidose) verificado no grupo obeso foram reduzidos com a suplementação com licopeno (Ob vs.Ob+Li). Esses dados sugerem que o licopeno pode representar uma estratégia terapêutica na atenuação da doença renal crônica e de alterações metabólicas associada à obesidade. Palavras chave: renal, doença, licopeno, obesidade, dieta hipercalórica, rato. Abstract Introduction: Obesity is related to the development of various diseases, including chronic kidney disease. Lycopene is a carotenoid present in tomatoes and other vegetables and is one of the most potent antioxidant compounds among carotenoids. Several studies have investigated the protective effect of lycopene in numerous diseases. However, to our knowledge, few studies have addressed the effect of lycopene on renal changes associated with obesity. Objective. The general objective of the present study will be to verify the influence of lycopene supplementation on renal biochemical, functional and morphological impairment in an experimental model of obesity induced by a diet rich in simple carbohydrates and saturated fat. Method. Wistar rats (n = 40) were randomized into two groups: Control (C, n=20) or Obese (Ob, n=20) hypercaloric diet rich in simple carbohydrate and saturate fat for 20 weeks. At week 20 renal failure was detected by urinary biochemical evaluation (proteinuria) and the animals were redistributed in 4 groups: Control group (C, n = 10); Control + Lycopene (C + Li, n = 10); Obese (Ob, n = 10) or Obese + Lycopene (Ob + Li, n = 10). Animals received corn oil (C, C + Li) or lycopene (10 mg / kg weight / day) (Ob, Ob + Li) via gavage for an additional 10 weeks. At week 30 they were submitted to 24-hour urine collection, systolic blood pressure measurement and euthanasia for blood and kidney collection and the following parameters were evaluated: adiposity index, plasma biochemical dosages (glucose, insulin, urea, creatinine, total protein, albumin, and urine (total protein, albumin, urea, creatinine), Homa-IR index calculation, renal oxidative damage biomarkers (protein carbonylation and lipoperoxidation), renal lycopene analysis and renal histological analysis. Results. The adopted diet model promoted obesity in the obese groups (Ob and Ob + Li) in relation to the control groups (C and C + Li). Obese animals (Ob and Ob + Li) exhibited a higher level of systolic blood pressure, serum glucose, and plasma albumin compared to the control groups (C and C + Li). Plasma insulin, HOMA-IR index, urinary protein / creatinine index, carbonylation of renal tissue proteins that were increased in animals in the obese group were reduced with lycopene supplementation (Ob vs Ob + Li). Renal histological analysis showed an increase in tubular fat deposition (lipidosis) in animals in the Obese group and decreased with lycopene supplementation (Ob vs Ob + Li). Conclusions. The adopted diet model promoted obesity (adiposity index), increased blood pressure, serum glucose, and plasma albumin without the influence of carotenoid supplementation. On the other hand, the increase in serum insulin, HOMA-IR index, urinary protein / creatinine index, renal protein carbonylation and renal fat deposition (lipidosis) observed in the obese group were reduced with lycopene supplementation (Ob vs.Ob + Li). These data suggest that lycopene may represent a therapeutic strategy to mitigate chronic kidney disease and metabolic changes associated with obesity. Keywords: renal, disease, lycopene, obesity, hypercaloric diet, rat.

Introduction: Obesity is related to the development of various diseases, including chronic kidney disease. Lycopene is a carotenoid present in tomatoes and other vegetables and is one of the most potent antioxidant compounds among carotenoids. Several studies have investigated the protective effect of lycopene in numerous diseases. However, to our knowledge, few studies have addressed the effect of lycopene on renal changes associated with obesity. Objective. The general objective of the present study will be to verify the influence of lycopene supplementation on renal biochemical, functional and morphological impairment in an experimental model of obesity induced by a diet rich in simple carbohydrates and saturated fat. Method. Wistar rats (n = 40) were randomized into two groups: Control (C, n=20) or Obese (Ob, n=20) hypercaloric diet rich in simple carbohydrate and saturate fat for 20 weeks. At week 20 renal failure was detected by urinary biochemical evaluation (proteinuria) and the animals were redistributed in 4 groups: Control group (C, n = 10); Control + Lycopene (C + Li, n = 10); Obese (Ob, n = 10) or Obese + Lycopene (Ob + Li, n = 10). Animals received corn oil (C, C + Li) or lycopene (10 mg / kg weight / day) (Ob, Ob + Li) via gavage for an additional 10 weeks. At week 30 they were submitted to 24-hour urine collection, systolic blood pressure measurement and euthanasia for blood and kidney collection and the following parameters were evaluated: adiposity index, plasma biochemical dosages (glucose, insulin, urea, creatinine, total protein, albumin, and urine (total protein, albumin, urea, creatinine), Homa-IR index calculation, renal oxidative damage biomarkers (protein carbonylation and lipoperoxidation), renal lycopene analysis and renal histological analysis. Results. The adopted diet model promoted obesity in the obese groups (Ob and Ob + Li) in relation to the control groups (C and C + Li). Obese animals (Ob and Ob + Li) exhibited a higher level of systolic blood pressure, serum glucose, and plasma albumin compared to the control groups (C and C + Li). Plasma insulin, HOMA-IR index, urinary protein / creatinine index, carbonylation of renal tissue proteins that were increased in animals in the obese group were reduced with lycopene supplementation (Ob vs Ob + Li). Renal histological analysis showed an increase in tubular fat deposition (lipidosis) in animals in the Obese group and decreased with lycopene supplementation (Ob vs Ob + Li). Conclusions. The adopted diet model promoted obesity (adiposity index), increased blood pressure, serum glucose, and plasma albumin without the influence of carotenoid supplementation. On the other hand, the increase in serum insulin, HOMA-IR index, urinary protein / creatinine index, renal protein carbonylation and renal fat deposition (lipidosis) observed in the obese group were reduced with lycopene supplementation (Ob vs.Ob + Li). These data suggest that lycopene may represent a therapeutic strategy to mitigate chronic kidney disease and metabolic changes associated with obesity
Influence of lycopene supplementation on renal impairment in diet-induced obesity in rats: analysis of the biochemical, functional and morphological profile
Keywords: Renal; Doença; Licopeno; Obesidade; Dieta hipercalórica; Rato; Disease; Lycopene; Obesity; Hypercaloric diet; Rat